Pengalihan Hak Atas Merek Kepada Ahli Waris Berdasarkan Surat Keterangan Waris - Pramitasari Pramitasari; Habib Adjie (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
A brand is a sign that can be displayed graphically in the form of an image, logo, name, word, letter, number, color arrangement, in 2 (two) dimensions and 3 (three) dimensions, sound, hologram, or a combination of 2 (two) or These elements are used to differentiate goods or services produced by individuals or legal entities in the field of trade in goods and/services. Redirection is a process, method, action, replacement, exchange, alteration. Meanwhile, rights are the power to do something (because it has been determined by law, applicable regulations, and authority according to law). In the case regarding the transfer of rights to a brand, a notary as a public official is authorized by law to make deeds. Notaries play a role in the distribution of inheritance in making deeds of inheritance statements and certificates of inheritance rights as supporting documents in the transfer of rights to registered trademarks based on inheritance, the registration of which must be through an application to the Minister.